Hubungan Bilateral Singapura - Timor Leste Pasca Penolakan Keanggotaan Timor Leste di ASEAN - Fredydara Ajiva Galateya; Satria Rizaldi Alchatib; Christy Damayanti (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2023)
This study aims to analyze the relationship between Singapore and Timor Leste in the aftermath of Singapore's rejection of Timor Leste in ASEAN membership. This research was conducted using qualitative methods and also using Regionalism Theory and Bilateral Theory. The results of this study indicate that there is a cooperative relationship between Singapore and Timor Leste, although Singapore refuses to accept Timor Leste who wants to join the ASEAN Organization. This of course becomes very difficult for Timor Leste because ASEAN is Timor Leste's hope to be able to develop its country with the help of ASEAN. However, Singapore feels burdened because the requirements to enter ASEAN membership have not been fulfilled by Timor Leste. Moreover, Singapore is the main pillar of the economy in ASEAN